State-of-the-art and perspectives of cutting edge preparation and its effect on the cutting performance of titanium alloy - Pan, Fangwei; Yuan, Haiyang (Frontiers in Materials, 2023)
Titanium alloys have been extensively used in industrial applications due to their unique mechanical and chemical properties. However, their low thermal conductivity and high chemical reactivity present considerable challenges in machining operations, leading to elevated cutting forces, fast tool wear, and inferior surface quality. To address these issues, advanced cutting edge preparation techniques have been devised to enhance the machining performance of titanium alloys. This paper offers an overview of the current state-of-the-art cutting edge preparation techniques for titanium alloy machining, and examines their effects on the machining performance. This paper first presents the characterization method of cutting edge geometry and then explores its effect on the machining performance, which evidences that judicious cutting edge preparation can notably enhance the machining performance by mitigating cutting forces and refining surface finish. It also emphasizes the underlying mechanisms of cutting edge preparation and their impacts on machining performance and subsequent cutting edge erosion. Finally, it concludes with perspectives of future research directions in this field, emphasizing the need to develop new cutting edge preparation techniques and optimize existing ones. Overall, this paper serves as a valuable resource for researchers and engineers seeking to improve the cutting performance of titanium alloys in various applications.